Impaired Pavlovian conditioned inhibition in offenders with personality disorders - He, Z.; Cassaday, Helen J.; Howard, Richard C.; Khalifa, Najat; Bonardi, Charlotte (2011)
Certain types of violent offending are often accompanied by evidence of personality disorders (PDs), a range of heterogeneous conditions characterised by disinhibited behaviours that are generally described as impulsive. The tasks previously used to show impulsivity deficits experimentally (in borderline personality disorder, BPD) have required participants to inhibit previously rewarded responses. To date, no research has examined the inhibition of responding based on Pavlovian stimulus-stimulus contingencies, formally ‘conditioned inhibition’ (CI), in PDs. The present study used a computer-based task to measure excitatory and inhibitory learning within the same CI procedure in offenders recruited from the ‘Personality Disorder’ and the ‘Dangerous and Severe Personality Disorder’ units of a high security psychiatric hospital. These offenders showed a striking and statistically significant change in the expression of inhibitory learning in a highly controlled procedure: the contextual information provided by conditioned inhibitors had virtually no effect on their pre-potent associations. Moreover, this difference was not obviously attributable to non-specific cognitive or motivational factors. Impaired CI would reduce the ability to learn to control associative triggers, and so could provide an explanation of some types of offending behaviour.